Design and validation of a noninvasive diagnostic criteria for biliary atresia in infants based on the STROBE compliant. Issue 6 (February 2019) - Liu, Xiaoguai; Peng, Xiaokang; Huang, Yanxia; Shu, Chang; Liu, Pan; Xie, Weike; Dang, Shuangsuo
Abstract : Abstract: It is difficult for clinicians to distinguish biliary atresia (BA) from other causes of neonatal cholestasis (NC) at an early stage. The aim of this study was to design and validate noninvasive diagnostic criterion for early diagnosis of BA in infants. In this retrospective cohort study, a total of 482 medical records of patients with NC were recruited to design diagnostic criteria. Parameters showing a significant difference between BA (n = 166) and non-BA (n = 316) patients were analyzed by logistic regression to predict the occurrence of BA, and then a nomogram scoring system was designed and validated in another cohort that included 190 cases of NC. A prediction diagnostic criterion with parameters including direct bilirubin, total bilirubin, globulin, albumin, gamma glutamyl transpeptidase, cholesterol, total bile acid, hepatobiliary scintigraphy, birth weight, and stool color was established; the sensitivity and specificity of this diagnostic criterion was 89% and 84%, respectively. The accuracy was 86% and the AUC was 0.91 [95% CI (0.88–0.97)]. The total score ranged from 0 to 402, with a cut-off value of ≥254 discriminating BA from other causes of NC. By applying this score in the validation set with age <60 days, the accuracy was 95.3%, the sensitivity was 93.8% and the specificity was 96.0%, respectively. This prediction diagnostic criterion could facilitate clinicians to distinguish infants with and without BA based on a particular series of parameters, reducing treatment burden and enhancing therapeutic efficiency. Abstract : Supplemental Digital Content is available in the text